Biological assessment of a new ready-to-use hydraulic sealer - Benetti, Francine [UNESP]; Gomes-Filho, Joao Eduardo [UNESP]; Azevedo-Queiroz, India Olinta de [UNESP]; Carminatti, Marina [UNESP]; Conti, Leticia Citelli [UNESP]; Reis-Prado, Alexandre Henrique dos; Penha de Oliveira, Sandra Helena [UNESP]; Ervolino, Edilson [UNESP]; Dezan-Junior, Eloi [UNESP]; Angelo Cintra, Luciano Tavares [UNESP] (Korean Acad Conservative Dentistry, 2021)
Objectives: This study compared the cytotoxicity, biocompatibility, and tenascin immunolabeling of a new ready-to-use hydraulic sealer (Bio-C Sealer) with MTA-Fillapex and white MTA-Angelus. Materials and Methods: L929 fibroblasts were cultivated and exposed to undiluted and diluted material extracts. Polyethylene tubes with or without (the control) the materials were implanted into the dorsa of rats. At 7 days and 30 days, the rats were euthanized, and the specimens were prepared for analysis; inflammation and immunolabeling were measured, and statistical analysis was performed (p < 0.05). Results: MTA-Fillapex exhibited greater cytotoxicity than the other materials at all time points (p < 0.05). The undiluted Bio-C Sealer exhibited greater cytocompatibility at 6 and 48 hours than white MTA-Angelus, with higher cell viability than in the control (p < 0.05). White MTA-Angelus displayed higher cell viability than the control at 24 hours, and the one-half dilution displayed similar results at both 6 and 48 hours (p < 0.05). At 7 days and 30 days, the groups exhibited moderate inflammation with thick fibrous capsules and mild inflammation with thin fibrous capsules, respectively (p > 0.05). At 7 days, moderate to strong immunolabeling was observed (p > 0.05). After 30 days, the control and MTA-Fillapex groups exhibited strong immunolabeling, the white MTA-Angelus group exhibited moderate immunolabeling (p > 0.05), and the Bio-C Sealer group exhibited low-to-moderate immunolabeling, differing significantly from the control (p < 0.05). Conclusions: Bio-C Sealer and white MTA-Angelus exhibited greater cytocompatibility than MTA-Fillapex; all materials displayed adequate biocompatibility and induced tenascin immunolabeling.
Keywords: Biocompatibility; Cytotoxicity; Hydraulic sealer; Mineral trioxide aggregate; Tenascin